CANDIDE et la monnaie - Aubry, Jean-Pierre; Duguay, Pierre (L'Actualité économique)

(untitled) (HEC Montréal, 1976)
AbstractIn this paper we deal with the financial sector of CANDIDE 1.1. We are concerned with the determination of the short-term interest rate, the term structure equations, and the channels through which monetary policy influences the real sector.The short-term rate is determined by a straightforward application of Keynesian liquidity preference theory. A serious problem arises from the directly estimated reduced form equation, which implies that the demand for high powered money, but not the demand for actual deposits, is a stable function of income and interest rates. The structural equations imply the opposite.In the term structure equations, allowance is made for the smaller variance of the long-term rates, but insufficient explanation is given for their sharper upward trend. This leads to an overstatement of the significance of the U.S. long-term rate that must perform the explanatory role. Moreover a strong structural hierarchy, by which the long Canada rate wags the industrial rate, is imposed without prior testing.In CANDIDE two channels of monetary influence are recognized: the costs of capital and the availability of credit. They affect the business fixed investment and housing sectors. The potential of the personal consumption sector is not recognized, the wealth and real balance effects are bypassed, the credit availability proxy is incorrect, the interest rate used in the real sector is nominal rather than real, and the specification of the housing sector is dubious.